Proceedings of the 2016 CHI Conference on Human Factors in Computing Systems 2016
DOI: 10.1145/2858036.2858593
|View full text |Cite
|
Sign up to set email alerts
|

Investigating Effects of Post-Selection Feedback for Acquiring Ultra-Small Targets on Touchscreen

Abstract: In this paper, we investigate the effects of post-selection feedback for acquiring ultra-small (2-4mm) targets on touchscreens. Post-selection feedback shows the contact point on touchscreen after a user lifts his/her fingers to increase users' awareness of touching. Three experiments are conducted progressively using a single crosshair target, two reciprocally acquired targets and 2D random targets. Results show that in average post-selection feedback can reduce touch error rates by 78.4%, with a compromise o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 29 publications
1
1
0
Order By: Relevance
“…While the checklist task was unaffected, longer completion times were observed for the flight plan edit task, especially with visual feedback. This confirms findings from previous studies where multimodal feedback either showed no effect or slowed down data entry (Bender, 1999;Yu et al, 2016). One likely explanation for the different effects on the two tasks is that, for the flight plan entry task, participants waited for feedback on each entry before proceeding to the next because of the larger variety of possible errors, unlike the checklist task where they either succeeded or failed to check off an item.…”
Section: Discussionsupporting
confidence: 86%
“…While the checklist task was unaffected, longer completion times were observed for the flight plan edit task, especially with visual feedback. This confirms findings from previous studies where multimodal feedback either showed no effect or slowed down data entry (Bender, 1999;Yu et al, 2016). One likely explanation for the different effects on the two tasks is that, for the flight plan entry task, participants waited for feedback on each entry before proceeding to the next because of the larger variety of possible errors, unlike the checklist task where they either succeeded or failed to check off an item.…”
Section: Discussionsupporting
confidence: 86%
“…Examples of improving touch accuracy include using an offset from the finger contact point [11,45,48], dragging in a specific direction to confirm an intended target among many items [2,39,59], visualizing a contact point [53,60], applying machine learning [51] or probabilistic modeling [9], and correcting hand tremor effects by using motion sensors [44]. In addition to these techniques, researchers have sought to understand why finger touch is less accurate compared with other input modalities such as a mouse cursor.…”
Section: Improvements and Principles Of Finger-touch Accuracymentioning
confidence: 99%